Penggunaan bahasa Melayu kreol Chetti Melaka: satu analisis domain (Jurnal Bahasa, 2001)
The speakers of the Malacca Chetties creole Malay is a unique group because although they are of Indian Tamil origin, the Malay dialect is their mother tongue. This study analysed the pattern of language choices amongst the speakers of this language based on selected do-mains. Fishman 's domain approach (1972) was adopted for this pur-pose. A total of seven domains namely, family, neighbourhood and friendship, religious, transactional, educational, occupational, and governmental domains were used. The findings of this study revealed that the Malacca Chetties creole Malay is extensively used in the fam-ily and religious domains